Valuing nature with travel cost models a manual - Ward, Frank A.; Beal, Diana J.; Edward Elgar Publishing (Cheltenham, U.K. ; Northhampton, Mass. : Edward Elgar, 2000)
The book presents a self-contained treatment of TCM along with a wide range of applications to natural resource and environmental policy questions.
1. Support for environmental policy decisions -- 2. History and scope of TCM -- 3. Demand theory and TCM -- 4. Benefits theory and TCM -- 5. Design principles for TCMs -- 6. Design and administration of surveys -- 7. Measurement of the variables -- 8. Data management and analysis -- 9. Developing and maintaining expertise.
Includes bibliographical references and index.
Keywords: Natural resources -- Management; Economic policy -- Decision-making.; Travel costs; Electronic books